Electric Stimulation at 448 kHz Modulates Proliferation and Differentiation of Follicle Dermal Papilla Cells - María Antonia Martínez-Pascual; Silvia Sacristán; Elena Toledano-Macías; María Luisa Hernández-Bule (Cosmetics)
Dermal papilla cells (DPCs) regulate the hair cycle and play important roles in hair growth and regeneration. Alopecia is a pathology caused by a deregulation in the hair cycle phases. Currently, the use of physical therapies such as radiofrequency (RF) as an alternative to pharmacological treatment is increasing. Electrical stimulation by capacitive resistive electrical transfer (CRET) is one of these therapies. The objective of the present study was to analyze the effect of RF-CRET currents on DPCs. Cells were treated with subthermal 448 kHz CRET currents with two different types of signals: standard (CRET-STD) or modulated (CRET-MOD). Viability (XTT Assay), proliferation (Ki67 and ERK1/2), apoptosis (p53 and caspase 3), differentiation (β-catenin and α-SMA), and anagen markers (versican and PPARγ) were analyzed by immunofluorescence and immunoblot. CRET caused effects on the proliferation and survival of DPCs associated with increases in the expression of p-MAPK-ERK1/2, cyclin D1, and decreases in the expression of p53 and caspase 3. Also, CRET caused significant transient increases in the expression of β-catenin, involved in hair growth, and in the expression of anagen phase markers such as versican and PPARγ related to hair follicle maintenance. The present study highlights the ability of treatment with CRET therapy to cause molecular alterations in DPC involved in hair regeneration.